Decision-Making Process of Thai Students In Choosing the UK Higher Education Institutions - Udomsinroj, Kayvalee (2013)
In the UK, the higher education is one of the largest markets that worth both the pecuniary and non-pecuniary benefits to the country. At present, the UK is among the most popular destination countries for the students, particularly the international students. However, nowadays the world’s higher education market has become increasingly highly competitive. Therefore, in order to sustain its high rank and attract more students, it is important for the UK higher education institutions to understand the decision-making process of students and design the effective marketing strategy. There have been a number of researches on the decision-making process of students from many countries. Unfortunately, none of them is done in the context of students from Thailand, one of the top ten non-EU senders in the UK higher education. The number of Thai students has been continually increasing in the recent years that make Thai students became the largest potential markets. Hence, it should be useful to investigate the decision-making process in the context of Thai students. The aim of this study is to explore the decision-making process of Thai students in choosing the UK higher education institutions, uncover the underlying influential factors, and design the potential marketing strategies in order to maintain the large number of and even attract more Thai students to the UK. In order to achieve the aim of this study, the qualitative in-depth semi-structured interview was employed. The primary data was collected from the total of fifteen participants, who were purposively selected from fifteen different universities in the UK to enhance the representativeness of the population. The template analysis was used to analyse the data and formed the final template to present the main findings of the study. The findings revealed that Thai students are encouraged to study abroad by the social status and the family influence. Then, after realising the need to study abroad, they consider the choice of country, city, institution, and programme simultaneously. The internet and the education fair are the most frequently-mentioned sources of information that Thai students use in the search phase. Then, in the selection phase, the university ranking and the entry requirements are the two main criteria that Thai students use to select a set of potential universities. After that, at the time the Thai students want to apply to the universities, the course contents will become an important factor. Additionally, the study pointed out that most of the Thai students rely on the agents in the application process. In the choice phase, the word-of-mouth spread by the alumni, the university ranking, and the location were found to be the important influential factors. Based on the findings, it could be said that in different phases along the decision-making process, Thai students are influenced by different factors. However, “ranking” can be claimed to be the most important influential factor for Thai students as it was found to influence Thai students in both the selection and the choice phase in the decision-making process. In accordance with all these findings, the 7Ps marketing mix strategy, consisting of programme, prominence, price, prospectus, people, promotion, and premiums, was eventually formed.